Priming Is Dispensable for NLRP3 Inflammasome Activation in Human Monocytes In Vitro - Gritsenko, Anna; Yu, Shi; Martin-Sanchez, Fatima; Diaz-del-Olmo, Ines; Nichols, Eva-Maria; Davis, Daniel M.; Brough, David; Lopez-Castejon, Gloria (Frontiers in Immunology, 2020)
Interleukin (IL)-18 and IL-1β are potent pro-inflammatory cytokines that contribute to inflammatory conditions such as rheumatoid arthritis and Alzheimer’s disease. They are produced as inactive precursors that are activated by large macromolecular complexes called inflammasomes upon sensing damage or pathogenic signals. NLRP3 inflammasome activation is regarded to require a priming step that causes NLRP3 and IL-1β gene upregulation, and also NLRP3 post-translational licencing. A subsequent activation step leads to the assembly of the complex and the cleavage of pro-IL-18 and pro-IL-1β by caspase-1 into their mature forms, allowing their release. Here we show that human monocytes are able to form canonical NLRP3 inflammasomes in the absence of priming. NLRP3 activator nigericin caused the processing and release of constitutively expressed IL-18 in an unprimed setting. This was mediated by the canonical NLRP3 inflammasome that was dependent on K+ and Cl- efflux and led to ASC oligomerisation, caspase-1 and Gasdermin-D (GSDMD) cleavage. IL-18 release was impaired by the NLRP3 inhibitor MCC950 and by the absence of NLRP3, but also by deficiency of GSDMD, suggesting that pyroptosis is the mechanism of release. This work highlights the readiness of the NLRP3 inflammasome to assemble in the absence of priming in human monocytes and hence the ability to contribute to the very early stages of the inflammatory response even when IL-1β has not been produced.